PELATIHAN PENANGANAN DASAR HEWAN COBA BAGI LABORAN BERBAGAI PERGURUAN TINGGI FARMASI DI PROVINSI NTB - Raisya Hasina; Siti Rahmatul Aini; Iman Surya Pratama; Mahacita Andanalusia; Yoga Dwi Saputra; Baiq Dwiyan Nugrahani; Yazid Maula Arzaqi (Universitas Mataram, 2023)
The use of experimental animals in drug research needs to be done before testing on humans. The increase in the use of experimental animals and ethical demands in pharmaceutical research have encouraged an increase in the capacity of laboratory staff in a sustainable manner, including in the Province of West Nusa Tenggara (NTB). Animal welfare greatly influences research results. The concept of welfare in question is